2018
DOI: 10.3389/fpls.2018.00338
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Depth Affects Phosphorus But Not Carbon and Nitrogen Concentrations of a Desert Phreatophyte in Northwest China

Abstract: Ecological stoichiometry is an important aspect in the analysis of the changes in ecological system composition, structure, and function and understanding of plant adaptation in habitats. Leaf carbon (C), nitrogen (N), and phosphorus (P) concentrations in desert phreatophytes can be affected by different depths of groundwater through its effect on the adsorption and utilization of nutrient and plant biomass. We examined the biomass, soil organic C, available (mineral) N, and available P, and leaf C, N, and P c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 59 publications
11
30
1
Order By: Relevance
“…Therefore, the SMC showed a positive significant relationship with the SOC and STN, ensuing in variations in leaf P contents due to interactive relationships among SOC, STN and STP. The results of the present study corroborated the findings of a recent study [ 33 ] that the source of plant nutrients was not merely soil but also groundwater/SMC. Furthermore, soil pH and SMC also affect concentration and storage of SOC, STN, and STP [ 81 , 87 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the SMC showed a positive significant relationship with the SOC and STN, ensuing in variations in leaf P contents due to interactive relationships among SOC, STN and STP. The results of the present study corroborated the findings of a recent study [ 33 ] that the source of plant nutrients was not merely soil but also groundwater/SMC. Furthermore, soil pH and SMC also affect concentration and storage of SOC, STN, and STP [ 81 , 87 ].…”
Section: Discussionsupporting
confidence: 91%
“…The pattern of leaf traits concentration for all 37 species was investigated ( Table 2 ). In the present study, it is noted that the mean leaf C concentration of all 37 plant species ( Table 2 ) was higher than that in leaves of plant species studied across the China [ 32 ], plants of the Taklamakan Desert [ 33 ] and especially higher than herbs of the Yucatan Mexico [ 34 ]. Results of the current study further investigated that the mean leaf N concentration ( Table 2 ) significantly higher than the global plants [ 35 ], China’s terrestrial ecosystems [ 32 ], herbs studied across China [ 36 ] and markedly lower than the KMUNR desert plants [ 37 ].…”
Section: Discussionmentioning
confidence: 58%
“…Due to this, SWC has a great impact on the levels of leaf P and N:P, and HCO 3 affects the production of leaf dry matter content. The result was supported by other observations [53].The changing C:P pattern along environmental gradients suggested that L. ruthenicum had a exible life strategy under different environments. In the deeper soil layer, HCO 3 -, followed by SO 4…”
Section: Trade-offs Between Functional Traits Of L Ruthenicumsupporting
confidence: 85%
“…Between them, SWC has larger contributions to leaf P content, N:P ratios and C:P ratios while HCO 3 has the greatest impact on LDMC, these can be inferred from previous research: In desert ecosystems, low soil moisture coupled with high soil alkalinity acts to decrease both soil N and P availability [52], Due to this, here SWC has a great impact on the levels of leaf P and N:P, and HCO 3 affects the production of dry matter content. Results which are partially supported by evidence from other observations [53]. Changing C:P pattern along environmental gradients suggests that L.…”
Section: Variations Of L Ruthenicum Leaf Functional Traits In the Losupporting
confidence: 83%